2019
DOI: 10.1055/s-0039-1693457
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Late Gadolinium Enhancement in Postoperative Morbidity following Mitral Valve Surgery in Rheumatic Mitral Stenosis

Abstract: Myocardial fibrosis in rheumatic mitral stenosis (MS) is caused by chronic inflammatory process. Its occurrence may lead to hemodynamic problems, especially after cardiac surgery. Myocardial fibrosis predicts worse morbidity after cardiac surgery, notably in coronary heart disease and aortic valve abnormalities. However, this issue has not been explored yet among patients with rheumatic MS.The aim of the study was to investigate prognostic impact of myocardial fibrosis to postoperative morbidity after mitral v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 37 publications
0
16
0
Order By: Relevance
“…Aschoff nodules are pathognomonic findings in RHD. Another study showed that preoperative myocardial fibrosis was identified in 91.5% of MS patients [12]. Myocardial fibrosis identified by late gadolinium enhancement (LGE) protocol was a nonischemic pattern, and most of them were described as patchy myocardial fibrosis that varied across every segment of LV [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Aschoff nodules are pathognomonic findings in RHD. Another study showed that preoperative myocardial fibrosis was identified in 91.5% of MS patients [12]. Myocardial fibrosis identified by late gadolinium enhancement (LGE) protocol was a nonischemic pattern, and most of them were described as patchy myocardial fibrosis that varied across every segment of LV [12].…”
Section: Discussionmentioning
confidence: 99%
“…Aschoff nodules are pathognomonic findings in RHD. Another study using magnetic resonance imaging (MRI) showed myocardial fibrosis in patients with rheumatic mitral stenosis (MS) who did not have ischemic heart disease [12]. This finding shows that there was an inflammatory process in the myocardium that eventually led to fibrosis.…”
Section: Introductionmentioning
confidence: 99%
“…This result is not very different from the results in some previous investigations that recruited a subset of patients similar to that in our research (91.5%). 14 However, other epidemiological studies regarding this topic have provided very different numbers. A previous study stated that the prevalence of myocardial fibrosis detected by necropsy analysis among patients with rheumatic heart disease (RHD) was only 19.9%.…”
Section: Discussionmentioning
confidence: 99%
“… 13 Furthermore, this issue is also applicable to patients with rheumatic MS who undergo mitral valve surgery as was described in previous publications with a similar subset of patients to this research. 14 Despite the established association between myocardial fibrosis and the clinical outcome after heart surgery, we still have no evidence whether it affects the LV anatomically.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation